The future of apprenticeships in Europe: three scenarios : Chapter 2 - Grollmann, Philipp [Verfasser]; Markowitsch, Jörg [Verfasser] (My University, 2021)
"The question addressed in this contribution is: How will apprenticeships in Europe develop and which types are likely to prevail? While this question has many aspects, three issues are deemed central: (a) the shape and purposes of institutionalised apprenticeship programmes in Europe. What is their main focus and design? A classification is used that was developed to capture and sort the multitude of apprenticeship programmes in European Member States; (b) the future training and recruitment decisions of firms: how far are firms willing to engage in formal education as a strategy of recruiting and developing skilled employees? Summaries are given of findings and concepts from the literature on economics of education and a research project on recruitment strategies of firms based on case studies in Germany, Spain, Italy, Portugal, Slovenia and the UK; (c) the future socio-political status of vocational education: which role and value will society attach to vocational education in the future and what is the role of apprenticeships in comparison to other forms of work-based learning? This section offers general scenarios on the future of VET from a recent Cedefop project. In the main part, the answers to the above three questions are integrated into three future scenarios for apprenticeships. The conclusion discusses the likeliness of the scenarios against the background of past and future trends in vocational education and work in Europe." (Authors' abstract, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 5.3 Personalentwicklung; T 1.5 International vergleichende Berufsbildungsforschung; I 2.2 Europa; 370; Berufsbildungssystem; Modellierung; Typologie; Zukunftsperspektive; Szenario; Personalgewinnung; Internationaler Vergleich; Europa